Gait performance of adolescent mice assessed by the CatWalk XT depends on age, strain and sex and correlates with speed and body weight - Pitzer, Claudia; Kurpiers, Barbara; Eltokhi, Ahmed (Scientific reports, 2021)
The automatization of behavioral tests assessing motor activity in rodent models is important for providing robust and reproducible results and evaluating new therapeutics. The CatWalk system is an observer-independent, automated and computerized technique for the assessment of gait performance in rodents. This method has previously been used in adult rodent models of CNS-based movement disorders such as Parkinson's and Huntington's diseases. As motor and gait abnormalities in neuropsychiatric disorders are observed during infancy and adolescence, it became important to validate the CatWalk XT in the gait analysis of adolescent mice and unravel factors that may cause variations in gait performance. Three adolescent wild-type inbred mouse strains, C57BL/6N, DBA/2 and FVB/N, were tested using the CatWalk XT (Version 10.6) for suitable detection settings to characterize several gait parameters at P32 and P42. The same detection settings being suitable for C57BL/6N and DBA/2 mice allowed a direct comparison between the two strains. On the other hand, due to their increased body weight and size, FVB/N mice required different detection settings. The CatWalk XT reliably measured the temporal, spatial, and interlimb coordination parameters in the investigated strains during adolescence. Additionally, significant effects of sex, development, speed and body weight within each strain confirmed the sensitivity of motor and gait functions to these factors. The CatWalk gait analysis of rodents during adolescence, taking the effect of age, strain, sex, speed and body weight into consideration, will decrease intra-laboratory discrepancies and increase the face validity of rodent models of neuropsychiatric disorders.
Gesehen am 24.08.2023